Peningkatan Pemberian ASI Ekslusif Melalui Pendidikan Kesehatan Tentang Kecukupan ASI - Nisa, Juhrotun; Baroroh, Umi; Fitrianingsih, Desy (Universitas Nusantara PGRI Kediri, 2022)
Adequate breastfeeding is very beneficial for the immune system, as well as the growth and development of babies, but the achievement of exclusive breastfeeding is still low. Knowledge is considered the most dominant factor in the success of breastfeeding, so this community service is carried out with the aim of increasing the knowledge of pregnant women about the adequacy of breastfeeding. The method used is the expert method in the form of health counseling related to exclusive breastfeeding, how to assess the adequacy of breast milk, production and demand for breast milk including expressed breast milk and how to increase milk production. The target of this activity is pregnant women at the Debong Lor Public Health Center. The result of this service activity is that there is an increase in the knowledge of pregnant women about the adequacy of breastfeeding. The data was obtained from the comparison of the results of the pretest and posttest. Health workers are expected to provide information about breastfeeding since pregnancy and the family can support exclusive breastfeeding.